Improvement of Crude Protein and Crude Fiber Digestibility of fermented Product of palm kernel cake and rice bran mixture for Broiler - Y. Sukrayana; U. Atmomarsono; V. D. Yunianto; E. Supriyatna (Jurnal Ilmu dan Teknologi Peternakan, 2011)
The research objective was to compare crude protein and crude fat digestibility of fermented product of palm kernel cake (80%) and rice bran (20%) mixture with those of unfermented product mixture. Student-t test was applied to determine the difference between the two treatments, while crude protein and crude fat digestibility were determined following the procedure of Coen et al. (1996). The results of the study showed that the crude protein digestibility of fermented product was higher (P<0.05) than that of unfermented product (84.96±2.43% vs 65.60±2.39%) or increased by 19.36%. The average crude fat digestibility increased (P<0.05), from 69.22±3.14% in the unfermented product to 85.08±2.04% in the fermented product or increased by 15.86%. In conclusion, process of fermentation significantly improved nutritive value of mixture of palm kernel oil (80%) and rice brand (20%) for broiler in terms of higher crude protein and crude fat digestibility.